PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. TELEFAST INDONESIA - Bambang Pujo Purwoko; Rian Saputra (Universitas La Tansa Mashiro, 2019)
Employee performance is very important for the success of a company as a whole so that business owners need employees who are able to complete work effectively for the creation of good performance, so we need performance support variables, namely the provision of compensation and motivation. This study aims to determine the effect of compensation and motivation on the performance of PT TELEFAST INDONESIA employees. Respondents in this study were all employees of PT TELEFAST INDONESIA.The method used by the author is a quantitative method. Sampling using incidental sampling method. Data collection using a questionnaire survey was carried out by going directly to the employees of PT TELEFAST INDONESIA Data obtained from 35 respondents from 40 questionnaires. The data obtained were analyzed using the SPSS version 20. The data analysis technique used to test the hypothesis was the Classical Assumption Formula method, Multiple Linear Regression Analysis, Correlation Correlation, Determination, Regression Coefficient Test Simultaneously or Simultaneously (Test f) and Test Partial Regression Coefficient (t test).The results of these tests are known to calculate the value of compensation variable tcount 5.734> t table 1.689. and sig 0,000 <0.05 This shows that compensation has a positive effect on employee performance. While the motivation is known the value of the t-count of the motivation variable is obtained t-count 4.955> t table 1.689 and sig 0.000 <0.05, This means that motivation partially influences employee performance. The results of Fcount and Ftable it can be concluded that Fcount> Ftable (106.585> 3.27) thus H3 is accepted meaning that there is a simultaneous influence between the compensation, motivation and employee performance variablesFrom this description it can be concluded that partial compensation affects employee performance, motivation partially influences employees and simultaneously compensation and motivation affect employee performance of PT TELEFAST INDONESIA.